2013
DOI: 10.1158/1535-7163.mct-12-1110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Chemical Targeting of Epithelial-Restricted with Serine Box Reduces EGF Receptor and Potentiates the Efficacy of Afatinib

Abstract: Epidermal growth factor receptor (EGFR) is elevated in over 90% of head and neck squamous cell carcinoma (HNSCC). However, a majority of HNSCC patients do not respond to anti-EGFR therapeutics. Insensitivity to EGFR inhibitors may be due to kinase-independent actions of EGFR and/or activation of Her2. Strategies to reduce EGFR and Her2 protein levels in concert may be an optimal approach to enhance the efficacy of current anti-EGFR molecules. In this study, knockdown of ESX decreased EGFR and Her2 promoter act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…To date, 20 manuscripts have been reported in the peer-reviewed literature assessing HER2 expression in HNSCC tumors (14-33). Six papers have evaluated HER2 targeting in HNSCC preclinical models, and 2 trials have been completed and reported using HER2 inhibitors for this malignancy (18, 34-40). In this review, we will evaluate the preclinical and clinical data implicating HER2 as a therapeutic target in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 20 manuscripts have been reported in the peer-reviewed literature assessing HER2 expression in HNSCC tumors (14-33). Six papers have evaluated HER2 targeting in HNSCC preclinical models, and 2 trials have been completed and reported using HER2 inhibitors for this malignancy (18, 34-40). In this review, we will evaluate the preclinical and clinical data implicating HER2 as a therapeutic target in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of ESX or EGFR induced a pleotropic anti-tumor effect in HNSCC (16). Our results showed that rescue of miR-124 to physiologic levels in HNSCC cells reduced ESX and EGFR.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that the predominant mechanism for EGFR dysregulation in HNSCC may be at the transcriptional level. Recent work from our laboratory revealed ESX as a transcription factor that modulates EGFR at the transcriptional level (16). Genetic ablation of ESX in ESX high /EGFR high HNSCC cells resulted in a reduced EGFR promoter activity and mRNA expression (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations